Compras hedônicas versus utilitárias: a influência do boca a boca eletrônico no processo de compra de smartphones - Santos, Denysleo Lopes dos (2015)
The understanding of the difference on the influence of the electronic word-ofmouth (eWOM) on smartphone's purchase in an hedonic and utilitarian perspective of consume is the main objective of this research. Regarding to finality, the research is considered basic pure, destined to intellectual satisfaction for knowledge, and also exploratory and descriptive. The data were collected through a semi structured questionnaire with the use of five point's Likert scale, to consumers from the local city who bought a smartphone in the last six months. The forms were apllied on shoppping centers, on different campuses from an university, on government departments and other places where consumers were accessible. After analysing the results from the research, the conclusion was that eWOM is important to consumer's buying decision, although on a lesser degree than the personal sources of information (friends and close family members). Besides, it was concluded that smartphone's hedonic and utilitarian attributes were both equally important to consumer's buying decision and it was difficult for them to dissociate these attributes to analyse their buying process.